Pembuatan film plastik biodegradable dari limbah kulit kopi dengan penambahan kitosan/gliserol - Edwin Rizki Safitra; Idra Herlina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2020)
Biodegradable plastic production has been developed for a long time by researchers. Data from Ministry of Industry in 2017 stated Indonesia's plastic production reached 3.9 million tons/ year. In this study, the raw materials used came from untapped waste, namely coffee skin, biodiesel-waste glycerol and shrimp-shells chitosan. In this research, biodegradable plastic films have been produced with the addition of glycerol and coffee skin waste with chitosan concentration variations of 0, 2, 4, 6, and 8%. After the optimum conditions were obtained by comparing the elongation and tensile strength values, then the variations in coffee skin waste were added with a weight of 0, 2, 4, 6, and 8 g. Tensile strength and elongation values with variations of chitosan were 0.2-1.87 MPa and 0.22-0.15%, respectively. Whereas the variation of tensile strength and elongation coffee skins were 1.8-0.27 MPa and 0.14-0.2%, respectively. The optimum conditions for producing biodegradable plastic films were obtained with variations of chitosan 4% and 2 g coffee skin with tensile strength and elongation values of 0.98 MPa and 0.16%. The tensile strength and elongation data produced from biodegradable plastic was still below the standard value of commercial plastic or synthetic plastic (HDPE) with values of tensile strength and elongation of 28.64 MPa and 6.5186% respectively.